IMPROVEMENT OF MODE OF THE ALLOYED BAR HEAT TREATMENT ON MILL 850 JSC «BMZ» – MANAGEMENT COMPANY OF HOLDING BMK - V. A. Lutsenko; T. N. Golubenko; P. A. Bobkov; L. A. Drobyshevsky; O. V. Lutsenko; A. S. Kozachek (Литьë и металлургия)
On the basis of the drawn card of the hardness values distribution according to the temperature and time parameters of heat treatment of chrome-molybdenic steel it is revealed that required values of hardness are reached at 680–650 °C within 4 hours. It is shown that decrease of hardness occurs due to large quantity of carbides which have changed their morphology.